Art beyond borders : artistic exchange in communist Europe (1945-1989) - Bazin, Jérôme, 1982-; Dubourg Glatigny, Pascal; Piotrowski, Piotr, 1952- (Leipzig studies on the history and culture of East-Central Europe, 2016)
"This book presents and analyzes artistic interactions between 1945 and 1989, both within the Soviet bloc and between it and the Western bloc. During the Cold War the exchange of artistic ideas and products united Europe's avant-garde in a most remarkable way. Through the Iron Curtain and through the national borders there was a constant flow of artists, artworks, artistic ideas and practices. But the geography of these exchanges still needs to be defined. How were networks, centres, peripheries (local, national and international), scales and distances constructed? What were the relations between the officially promoted socialist realism and the (neo)avant-garde tendencies? The slowly expanding literature on the art of Eastern Europe in western European languages provides a great deal of factual knowledge about a vast cultural space mostly through the prism of stereotypes and in national compartments. By discussing artworks, studying the writings on art, reconstructing trajectories and artists' strategies, as well as the influence of political authorities, art dealers and art critics, the essays in Art beyond Borders compose a transnational history of arts in the Soviet satellite countries."--Publisher description